Bago City Penal Farm the Negros Occidental correctional facility for minimum security inmates - Sison, Ina Mae S.; Santos, Maria Lisa V. (Quezon City College of Architecture, University of the Philippines Diliman, 2019)
Local penitentiaries are extremely congested. Most lack adequate and quality spaces for inmate accommodation and various livelihood activities. Improving these facilities may help aid in reducing recidivism and promote productive lifestyles among pre-release prisoners. This project addresses those concerns through a proposed design for a minimum-security compound in Bago, Negros Occ. The facility may also further the technological and economical progress in Western Visayas.
include appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Prison facilities -- Philippines